Impact of Shopping Experience on Consumer Loyalty: An Empirical Study of Organized and Unorganized Retailers in India - Zia, Adil (ASPENSI in Bandung, Indonesia, 2014)
ABSTRACT: Indian retail is a mix, or organized as well as unorganized, in retail stores. Shopping experience plays an important determinant factor of consumerâs loyalty, irrespective of type of retail store (organized or unorganized). Favorable shopping experience leads to positive propensity towards consumersâ loyalty, whereas unfavorable shopping experience leads to dis-loyalty. This paper is an attempt to know the impact of shopping experience on consumerâs loyalty in an organized as well as unorganized retails setup. SEM (Structural Equation Modeling) technique was applied on a sample of 706 consumers to know the impact of various factors of shopping experience on consumer loyalty. The results indicate that all the three factors of shopping experience, considered for the study, have positive impact on consumer loyalty, namely: ERE (Executional Related Excellence), E (Expediting), and PR (Problem Recovery). The ERE, which means patiently explanation and advice, checking stock, helping find products, having product knowledge, and providing unexpected product quality, has the least impact on consumer loyalty. The E, which connotes being sensitive to customersâ time and long check-out lines, and being pro-active in helping speed up the shopping process, has the highest impact on consumer loyalty. While the PR, which means helping resolve and compensate for problems, upgrading quality, and ensuring complete shopper satisfaction, has the least impact on consumer loyalty.KEY WORD: Shopping experience, consumer loyalty, organized and unorganized retailers, executional related excellence, expediting, and problem recovery.Â RESUME: âDampak Pengalaman Belanja atas Loyalitas Konsumen: Sebuah Studi Empiris tentang Pengecer Terorganisir dan Tak Terorganisir di Indiaâ. Pengecer India adalah campuran, atau baik terorganisir (modern) maupun tak terorganisir (tradisional), dalam toko-toko eceran. Pengalaman belanja merupakan faktor penentu dan penting bagi loyalitas konsumen, terlepas dari jenis toko eceran (terorganisir atau tak terorganisir). Pengalaman belanja yang menguntungkan menyebabkan kecenderungan positif terhadap loyalitas konsumen, sedangkan pengalaman belanja yang tidak menguntungkan menyebabkan ketidakloyalan konsumen. Makalah ini merupakan upaya untuk mengetahui dampak dari pengalaman belanja terhadap loyalitas konsumen yang dirancang dalam toko-toko eceran teorganisir dan tak terorganisasir. Teknik-teknik SME (Model Kesamaan Struktural) diterapkan pada sampel sebanyak 706 konsumen untuk mengetahui dampak dari berbagai faktor pengalaman berbelanja terhadap loyalitas konsumen. Hasil penelitian menunjukkan bahwa semua tiga faktor pengalaman belanja, yang dipertimbangkan dalam penelitian ini, berdampak positif terhadap loyalitas konsumen, yaitu: ERE (Pelaksanaan Terkait Keunggulan), E (Kecepatan), dan PR (Pemulihan Masalah). Faktor ERE, yang berarti dengan sabar memberikan penjelasan dan saran, memeriksa stok, membantu menemukan produk, memiliki pengetahuan produk, dan menyediakan kualitas produk yang tak terduga, memiliki dampak paling sedikit pada loyalitas konsumen. Faktor E, yang berkonotasi sensitif terhadap waktu pelanggan dan panjang garis untuk keluar, serta menjadi pro-aktif dalam membantu mempercepat proses belanja, memiliki pengaruh paling tinggi terhadap loyalitas konsumen. Sementara faktor PR, yang berarti membantu menyelesaikan dan mengkompensasi masalah, meningkatkan kualitas, dan menjamin kepuasan pembeli, memiliki dampak paling sedikit pada loyalitas konsumen.KATA KUNCI: Pengalaman belanja, loyalitas konsumen, pengecer terorganisir dan tak terorganisir, pelaksanaan terkait keunggulan, kecepatan, dan pemulihan masalah.About the Author: Dr. Adil Zia is working as an Assistant Professor at the Department of Business Administration, Murshidabad Centre AMU (Aligarh Muslim University), Uttar Pradesh, India. His areas of interest include Research Methods, Consumer Behavior & Marketing Management. E-mail address: adilzia@live.comHow to cite this article? Zia, Adil. (2014). âImpact of Shopping Experience on Consumer Loyalty: An Empirical Study of Organized and Unorganized Retailers in Indiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.7, No.1 [Mei], pp.134-144. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, UNHAS Makassar, and UNIPA Surabaya, ISSN 1979-0112. Chronicle of article: Accepted (March 19, 2014); Revised (April 26, 2014); and Published (May 20, 2014). Â Â